2019
DOI: 10.1371/journal.pone.0219544
|View full text |Cite
|
Sign up to set email alerts
|

Parental assessment of physical education in the school curriculum: A brief report on the influence of past experiences as students

Abstract: The aim of this study was to analyse the relationship between parents' past experience as Physical Education (PE) students and the importance they give to PE within the school curriculum. Parents of 1834 teenagers from Spain and Portugal participated in the study (1834 fathers and 1834 mothers). An 11 item questionnaire was used for data collection. The measures studied were: socio-demographic characteristics, parent´s past experience as PE students, and importance that parents gave to PE in the school curricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(48 reference statements)
0
2
0
1
Order By: Relevance
“…The International Students’ Lifestyle Questionnaire (LSQ), previously used in numerous studies [ 31 , 32 , 33 , 34 ], was used as the data collection instrument. This questionnaire comprises 39 closed-ended questions, structured in 4 dimensions: (1) personal data (6 items), (2) lifestyle habits (12 items), (3) attitudes and perceptions (12 items), and (4) evaluation of school, physical education and PA (9 items).…”
Section: Methodsmentioning
confidence: 99%
“…The International Students’ Lifestyle Questionnaire (LSQ), previously used in numerous studies [ 31 , 32 , 33 , 34 ], was used as the data collection instrument. This questionnaire comprises 39 closed-ended questions, structured in 4 dimensions: (1) personal data (6 items), (2) lifestyle habits (12 items), (3) attitudes and perceptions (12 items), and (4) evaluation of school, physical education and PA (9 items).…”
Section: Methodsmentioning
confidence: 99%
“…PE classes reflect the pre-defined curriculum, and parents' views are important in developing school PE policies and curriculum. Lago-Ballesteros et al [44] concluded that parents generally like PE, but their views on whether it should be mandatory and assessed as part of the curriculum vary. PE teachers are responsible for delivering PE lessons to the students and to society.…”
Section: Theme 1 Educating the Publicmentioning
confidence: 99%
“…(2) Valoración de la escuela (no me gusta nada, no me gusta mucho, me es indiferente, me gusta, me gusta mucho); (3) Valoración de la EF (no me gusta nada, no me gusta mucho, me es indiferente, me gusta, me gusta mucho); funcionalidad que le otorgan a la EF (libera energías, promueve aprendizajes o perfeccionamiento de las técnicas deportivas, enseña a tener una buena conducta moral, promueve estilos de vida activos y saludables, proporciona momentos de relajación y diversión, mejora la condición física). (Marques et al, 2017;Lago-Ballesteros et al, 2019).…”
Section: Variables De Estudiounclassified